Political Contribution and Ideology of Acharya Naredra Deva - Kumar, Prof. Kamal (The journal of contemporary issues in business and government, 2021)
The Congress Socialist Party in early 1930s played a significant role in Indian nation political movement. It contributed to the socio- economic radicalism and political militancy and succeeded in making socialism as political agenda of development and struggle for the Independence . The Indian Social Movement was led mainly by Acharya Narendra Deva, Ram Monohar Lohia and Jayaprakasah Narayan , Acharya Narendra Deva was strong believer that the political leadership must give the “Congress and the national movement a socialist direction and in order to achieve the objective they must organise the workers and peasants in their class organisations and make them the social base of the anti imperialist struggle.” The contribution of Acharya Narendra Deva in Indian Socialism and shaping the political movement during 1930s and 1940s has been quite significant while his role as Educationalist in early 1950s paved the Gandhian path of development of higher education and social development. Archarya Narendra Deva is also known as Socialist Political Thinker and his ideas are still relevant . Against this backdrop, present paper highlights the role and contribution of Acharya Narendra Deva in contemporary Indian political movement and highlighting his socio- political ideas.